Pengaruh Layanan Bimbingan Kelompok dengan Teknik Self-Management Terhadap Intensitas Kecanduan Game - Nurul Jannah; Winda Ade Ariani; Widya Kartika Sari (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to reduce game addiction of class XI IPS students of SMA Negeri 1 Bengkulu Tengah through group guidance services with self-management techniques. These services and techniques aim to assist students in managing their own behavior to change it, especially in game addiction. This study uses a quasi-experimental research method (quasi-experimental). The population in this study were students of SMA Negeri 1 Bengkulu Tengah. Sampling using purposive sampling technique with one group consisting of 10 people. The selection is based on the criteria for game addiction which is in the high category. Data collection using a game addiction questionnaire. The data analysis technique used descriptive percentage. The results of the analysis obtained that the average value of students' game addiction for the pretest was 108.90 in the high category. While the average value of student game addiction for the posttest is 74.00 in the low category. Thus, descriptively it can be said that there is a decrease in the average value of game addiction between the pretest and posttest. To test the hypothesis, the Mann Withney test was used. The results of the study obtained that group guidance with self-management techniques was very effective in reducing the intensity of game addiction in students.